Systemic Functional Grammar & Natural Language Generation : Linguistic Description and Computational Representation. - Teich, Elke (Communication in artificial intelligence., 1999)
This volume deals with the computational application of systemic functional grammar (SFG) for natural language generation. In particular, it describes the implementation of a fragment of the grammar of German in the computational framework of KOMET-PENMAN for multilingual generation. The text also presents a specification of explicit well-formedness constraints on syntagmatic structure which are defined in the form of typed feature structures. It thus achieves a model of systemic functional grammar that unites both the strengths of systemics, such as stratification, functional diversification.